ExoPD-L1: an assistant for tumor progression and potential diagnostic marker - Hu, Rong; Jahan, Md Shoykot; Tang, Lijun (Frontiers in Oncology, 2023)
The proliferation and function of immune cells are often inhibited by the binding of programmed cell-death ligand 1 (PD-L1) to programmed cell-death 1 (PD-1). So far, many studies have shown that this combination poses significant difficulties for cancer treatment. Fortunately, PD-L1/PD-1 blocking therapy has achieved satisfactory results. Exosomes are tiny extracellular vesicle particles with a diameter of 40~160 nm, formed by cells through endocytosis. The exosomes are a natural shelter for many molecules and an important medium for information transmission. The contents of exosomes are composed of DNA, RNA, proteins and lipids etc.They are crucial to antigen presentation, tumor invasion, cell differentiation and migration. In addition to being present on the surface of tumor cells or in soluble form, PD-L1 is carried into the extracellular environment by tumor derived exosomes (TEX). At this time, the exosomes serve as a medium for communication between tumor cells and other cells or tissues and organs.In this review, we will cover the immunosuppressive role of exosomal PD-L1 (ExoPD-L1), ExoPD-L1 regulatory factors and emerging approaches for quantifying and detecting ExoPD-L1.More importantly, we will discuss how targeted ExoPD-L1 and combination therapy can be used to treat cancer more effectively.